2009
DOI: 10.1111/j.1469-8749.2008.03157.x
|View full text |Cite
|
Sign up to set email alerts
|

Psychometric properties of the Pediatric Motor Activity Log used for children with cerebral palsy

Abstract: The Pediatric Motor Activity Log (PMAL) is a parent‐report measure of the use, by children with hemiplegic cerebral palsy (CP), of their affected upper limb in everyday activities. The aim of this study was to examine the psychometric properties of both scales of the PMAL (‘How Often’ and ‘How Well’ scales) using Rasch measurement modelling. Sixty‐one parents of children with hemiplegic CP completed the PMAL and 31 completed it again 3 weeks later. The mean age of children was 4 years 6 months (SD 1y 9mo); 35 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
67
0
7

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(74 citation statements)
references
References 20 publications
0
67
0
7
Order By: Relevance
“…57 The original version 6 lacks sufficient evidence of reliability and validity. Subsequently, a revised version submitted to Rasch analysis was reported 58 in addition to a second alternative revision. 59 Both revisions were called PMAL-R, causing confusion over the version used in each study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…57 The original version 6 lacks sufficient evidence of reliability and validity. Subsequently, a revised version submitted to Rasch analysis was reported 58 in addition to a second alternative revision. 59 Both revisions were called PMAL-R, causing confusion over the version used in each study.…”
Section: Discussionmentioning
confidence: 99%
“…A further validity study of the original PMAL found only fair criterion validity for the how well domain (how well the child uses their impaired UL) but suggested that the measure was markedly sensitive to change. 60 Because each version of the PMAL, however, has different items, rating scales, mode of administration, and overall limited psychometric data, 58 we chose to exclude these data from meta-analysis. Future studies using the PMAL to evaluate realworld use of the impaired UL should accurately cite the relevant version used.…”
Section: Discussionmentioning
confidence: 99%
“…Both scales, which range from 0-5, are anchored at six points by abbreviated phrases and longer definitions; interviewees may select scores halfway between the anchors. Conversion for HW items scores (0, 1, or 2 = 0; 3 = 1; 4 or 5 = 2) and HO item scores (0 or 1 = 0; 2 or 3 = 1; 4 or 5 = 2) based on the mean of the item scores used to derive the total scores for each scale [13]. The PMAL-R had high internal consistency and Convergent validity was supported by a strong correlation between changes in PMAL-R scores and more-affected arm use during play which verify The PMAL-R interview as a reliable and valid measure of upper-extremity pediatric neurorehabilitation [14].…”
Section: Asmaa Osama Sayed Et Al Constraint Induced Movement Therapymentioning
confidence: 99%
“…Wallen et al (2008) Stewart et al (2010), foi avaliado um teste australiano que auxilia cuidadores a acessar informações, organizar ideias e se comunicar a respeito da criança. Já Fingerhut (2009), desenvolveu o Life Participation for Parents (LPP), que avalia a satisfação dos pais em relação à sua própria eficiência e eficácia na participação em muitas esferas da vida, enquanto criam uma criança com deficiência.…”
Section: Sobre a Avaliação Em Terapia Ocupacionalunclassified
“…Alguns artigos demonstraram a tendência do uso de abordagens centradas na família (CUSICK; LANNIN; LOWE, 2007;FINGERHUT, 2009;GALVIN et al, 2010;HARRIS;DANIELS, 1996;HOYT-HALLETT et al, 2009;MAJNEMER;ROSENBLATT, 1994;STEWART et al, 2010;WALLEN et al, 2008). Segundo Galvin et al (2010) esta prática está baseada na idéia de que os pais são os especialistas quando se trata de sua criança e de que cada família é única.…”
Section: A Importância Dos Relatos Dos Pais Como Método Avaliativounclassified